Différenciation génétique à fine échelle d'ombles chevaliers anadromes (Salvelinus alpinus) entre des frayères d'un même bassin versant au Nunavut - Sévigny, Maude (Université Laval, 2021)
The presence of several genetically differentiated populations with different phenotypic characteristics, termed biocomplexity, can have a positive impact on the profitability and sustainability of fisheries. Recently, acoustic telemetry and genomic data provided evidence that anadromous Arctic Char (Salvelinus alpinus) on southern Victoria Island, Nunavut, generally home to natal rivers for spawning yet the prevalence of intra-system philopatry remains unclear. The main objective of this study was to assess the potential for finer-scale homing that is, to specific spawning locations within the Ekalluk River watershed which supports the largest active commercial quota for Arctic Char in Canada. More specifically, using genomic approaches, the project aimed to: (1) test for the presence of significant genomic differentiation among spawning stocks within the watershed; (2)look for highly differentiated markers which may suggest the potential for local adaptation; and (3) validate the presence of philopatry to spawning locations using acoustic telemetry. Genomic data (genotyping by sequencing, 14,617 single-nucleotide polymorphism (SNPs) markers) for Arctic Char from five different lakes revealed weak but significant population structure (mean pairwise F[indice ST] = 0.013). Population assignment success was generally high assigning individuals to their capture location (overall mean of 91.55% success rate) indicating that the development of a mixed-stock fishery genomic-derived tool is possible (assuming all possible locations of origin are sampled). We also identified highly differentiated genomic regions that could potentially be under selection, thus indicating the possibility of within-watershed local adaptation - a hypothesis that would require more data to test appropriately. Finally, the acoustic telemetry data obtained from 82 tagged fish from four different locations indicated great variability in individual movements among the habitats used for foraging, spawning and overwintering, indicating that, while ...